The ambiguous mystery - Abdul Razak, Mariatulqabtiah; Buttigieg, Karen (Universiti Putra Malaysia Press, 2016)
Zika virus is not new. The first case of human infection was detected in Uganda and Tanzania in 1952. This flavivirus was associated with diseases in 1964. The virus is spread mainly by the bite of an infected mosquito, and may also be transmitted sexually.